Learning Translation and Multi-culture to Reduce Social Conflict - Aris Wuryantoro (Universitas PGRI Madiun, 2020)
This study aims to describe the role of learning translation with enhancing multi-culture understanding to reduce social conflict in society. This study used descriptive qualitative method by using documentation technique in collecting data. The source of the data are documentations in the form of intralingual and interlingual translation. The result of the study reveals that translation has four aspects, there are meaning, grammatical structure, communication situation, and cultural context. Besides, translation is closely related to cultural context aspect because translation contains at least cultural aspect from source language and target language. The researchers conclude that learning translation can enhance multi-culture in order to reduce social conflicts. The language used by one society automatically shows its language user or its social identity. The researcher concludes that by mastering language and culture of one society as a part of learning translation, we can reduce social conflict which mainly caused by misunderstanding toward the used language and culture.